Pengaruh Model Pembelajaran Structured Dyadic Methods (SDM) menggunakan Media Real Object terhadap Hasil Belajar Siswa pada Materi Pedosfer di MA Ruhul Islam Anak Bangsa - Safrijal Safrijal; Fitriani Yulianti; Cut Vita Rajiatul Jummi (Jurnal Pendidikan Geografi Undiksha, 2026)
The problems in geography learning are the low level of student activity, limited variation of learning models, and minimal use of media, which negatively affect learning outcomes. The Structured Dyadic Methods (SDM) learning model was chosen because it actively engages students in pair-based learning, while real object media provides direct learning experiences that strengthen conceptual understanding. The research problem of this study is whether the SDM model assisted with real object media has an effect on students’ learning outcomes in Pedosphere material, with the aim of improving student achievement at MA Ruhul Islam Anak Bangsa. This research employed a quantitative approach with a quasi-experimental method and a nonequivalent control group pre-test-post-test design. The research instrument was a multiple-choice test that had been validated for validity and reliability, and the data were analyzed using normality, homogeneity, and t-test analyses. The results showed that the value of tcount = 12.24 was higher than ttable = 1.671 at a 5% significance level. Thus, it can be concluded that there is a significant effect of the SDM learning model assisted with real object media on students’ learning outcomes compared to the Think Pair Share (TPS) learning model.